2012
DOI: 10.1159/000338086
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Lactate: Is There a Role for Serum Lactate Measurement in Diagnosing Acute Mesenteric Ischemia?

Abstract: Background/Aims: Measurement of serum lactate remains the most frequently applied laboratory investigation to diagnose acute mesenteric (intestinal) ischemia. The present review aims at critically questioning the widespread measurement of serum lactate to diagnose acute mesenteric ischemia in clinical practice and at drawing attention to more novel markers of intestinal ischemia. Methods: An electronic search of multiple databases was performed with the key words ‘lactate’, ‘marker’, ‘mesenteric’, ‘intestinal’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 119 publications
4
88
1
3
Order By: Relevance
“…In a study by Demir et al, 30 done for identifying factors predicting the need for surgery, elevated CRP was significantly associated with bowel gangrene and an underlying predictive value for the need of surgery. Another study by Lin et al 31 for evaluation of risk factors for intestinal gangrene identified that elevated serum CRP was associated with bowel gangrene.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Demir et al, 30 done for identifying factors predicting the need for surgery, elevated CRP was significantly associated with bowel gangrene and an underlying predictive value for the need of surgery. Another study by Lin et al 31 for evaluation of risk factors for intestinal gangrene identified that elevated serum CRP was associated with bowel gangrene.…”
Section: Discussionmentioning
confidence: 99%
“…Murray et al demonstrated a significant correlation between the elevation of D-lactate levels and the tissue injury seen in rat models of acute intestinal ischaemia [102]. However, whilst D-lactate may have increased specificity compared to L-lactate in this condition, there is still not enough data to show that it is reliable enough to be used for the diagnosis of acute mesenteric ischaemia [103].…”
Section: The Clinical Significance Of D-lactatementioning
confidence: 99%
“…(13,21,22) Several prospective clinical studies on lactate levels andacute mesenteric ischemia were conduct , from these studies the two studies conduct 1994 and 1997 by Lange and Jackel and also Lange and Toivola where the authors concluded that even with the high sensitivity of serum lactate the specificity was low which mean that doctors couldn't rely on serum lactate as specific markers. (7,23,24), during the last few years the number of prospective studies comparing the accuracy of several biomarkers were increased and demonstrated the fact that that none of the using biomarkers had the level of accuracy to be used alone as diagnostic markers. (25,26), in 2015 a study was conduct to assess the accuracy of repeated measurement of serum lactate as a marker and the authors reported that there are several factors influenced this accuracy.…”
Section: And6and Figures 56 And7)mentioning
confidence: 99%
“…(12) The results of current study consistence with previous study results that serum lactate is not accurate as the doctors want and need to be combine with other markers to diagnose AMI, however still a lot of doctors rely on serum lactate as diagnostic tool due to the facts that there is no good biomarkers could replace it, it is easy to measure in any laboratory hospital and easy to repeat it . (7,12) During 2009 Evennett et alconduct acomparative analysis study of all major serum markersof acute mesenteric ischemia and they demonstrated D -lactate as the best markers ,(6,7) after that in 2015 study conducted by the authors reported that the D-lactate is a good markers for sever cases with high level of specificity , and recommend to combine it with I-FABP which has high sensitivity and low specificity. (11) …”
Section: And6and Figures 56 And7)mentioning
confidence: 99%
See 1 more Smart Citation